Effects of different concentrations of pineapple core extract and maceration process on free-range chicken meat quality - Hussain, Norhayati; Choy, Hew Weng; Munawar, Nursabrina (Codon Publications, 2022)
The tenderisation effects of pineapple (Josephine variety) core extracts on the quality of free-range chicken meat using different maceration concentrations (30%, 50%, and 100%) and duration (15, 25, and 35 min) were analysed. Texture profile analysis, colour, pH, bromelain content, and microbiological analyses of the macerated meat samples were assessed. Broiler breast meat macerated with core extract (100%, 35 min) showed 86% reduction in hardness and the pH decreased from 5.87 to 4.99. The pineapple core extract has great potential as a meat tenderiser thus reduces the agriculture by-product and converts it into natural food ingredients.